Impact of IS26 mobilization on genetic manipulation of multidrug-resistant Acinetobacter baumannii - Hu, Yuan; Zheng, Junjie; Gong, Yanan; He, Lihua; Meng, Fanliang; Zhang, Jianzhong (Frontiers in Microbiology, 2025)
IntroductionMultidrug-resistant Acinetobacter baumannii poses significant challenges for genetic manipulation, historically hindering research on this organism.MethodsTo elucidate the factors contributing to these difficulties, comA and xcpW knockouts were performed on a multidrug-resistant (MDR) clinical isolate of international clone 2 (IC2), designated HN85.ResultsThrough electroporation, both constructed telR-marked suicide plasmids were recruited via active IS26 transposition into adjacent genomic regions, complicating attempts to delete the target genes through homologous recombination. Transferred by natural transformation and conjugation methods, the suicide plasmids successfully evaded targeting by IS26 and ultimately achieved comA and xcpW knockouts. During mutant screening following transformation, false positive colonies consistently emerged on tellurite plates without undergoing plasmid integration. Genomic sequencing revealed that this tellurite resistance resulted from the interruption of pitA caused by IS26 transposition. To investigate whether the high transposition activity of IS26 was attributable to its high copy number in HN85, a single IS26 copy was introduced into a susceptible clinical A. baumannii isolate W068. Although W068 possesses a higher density of insertion sequence (IS) elements, IS26 remained preferentially mobilized and exhibited similar active transposition behavior in the new host cell.DiscussionIS26 is prevalent in A. baumannii genomes (78.1%, 698/931), particularly among strains belonging to IC2 (99.8%, 509/510), implying its significant role in the evolution and success of IC2. The potential implications of active IS26 transposition for gene editing and screening warrant careful consideration beyond just A. baumannii.